Animacy effects extend to working memory: results from serial order recall tasks. Issue 2 (7th February 2020) - Daley, Matthew J.; Andrews, Glenda; Murphy, Karen
ABSTRACT: Words that represent animate entities (e.g., dog) are recalled from long-term memory more accurately than words representing inanimate entities (e.g., pan). In this research, we examined whether the animacy effect extends to working memory (WM). The potential roles of WM maintenance strategies (rehearsal and directed attention) were also examined. Participants performed serial order recall tasks with sets of 3, 4, 5 or 6 words that were either animate or inanimate. In stage 1 of Experiment 1, participants received no instructions regarding how to maintain the words. In stage 2, participants received either no instructions, sub-vocal rehearsal or directed attention instructions. In all instruction groups and at both stages, significant animacy effects were observed at set sizes of 4, 5 and 6 but not set size 3. The animacy effect was larger at set size 5 than other set sizes. In Experiment 2, participants completed the task with and without articulatory suppression. In both conditions, animacy effects were observed at set sizes 4, 5 and 6, but not at set size 3. The magnitude of the animacy effect declined as set size increased from 4 to 6. Animacy appears to enhance serial recall, but the effect is not dependent on rehearsal.